2014
DOI: 10.1371/journal.pone.0111429
|View full text |Cite
|
Sign up to set email alerts
|

Functional Coupling of a Nematode Chemoreceptor to the Yeast Pheromone Response Pathway

Abstract: Sequencing of the Caenorhabditis elegans genome revealed sequences encoding more than 1,000 G-protein coupled receptors, hundreds of which may respond to volatile organic ligands. To understand how the worm's simple olfactory system can sense its chemical environment there is a need to characterise a representative selection of these receptors but only very few receptors have been linked to a specific volatile ligand. We therefore set out to design a yeast expression system for assigning ligands to nematode ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Tehseen et al demonstrated that the Caenorhabditis elegans olfactory GPCR ODR-10 was functionally expressed in yeast by using chimeric Gpa1/C. elegans Gα [97]. Mukherjee et al constructed a medium-chain fatty acid biosensor by using the olfactory receptor OR1G1 that functionally expressed in yeast [98].…”
Section: Peripheral Membrane Proteinsmentioning
confidence: 99%
“…Tehseen et al demonstrated that the Caenorhabditis elegans olfactory GPCR ODR-10 was functionally expressed in yeast by using chimeric Gpa1/C. elegans Gα [97]. Mukherjee et al constructed a medium-chain fatty acid biosensor by using the olfactory receptor OR1G1 that functionally expressed in yeast [98].…”
Section: Peripheral Membrane Proteinsmentioning
confidence: 99%
“…A technique that is capable of onsite VOC collection and detection would allow law enforcement agencies to rapidly assess potentially hazardous conditions and aid investigators in analysing VOCs in laboratories. One potential method for onsite detection is the use of biosensors that are capable of detecting targets in the liquid phase, and thus, a system that collects VOCs from a liquid substrate could be a potential method of onsite analysis [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Yeast cultures, which can be grown rapidly and at low cost, are ideal for use in automated screens [ 8 11 ]. Yeast cells are suitable hosts for the expression of nematode proteins [ 12 18 ], including enzymes essential for different life-cycle stages of the parasites, many of which cannot be propagated in vitro [ 17 ]. We engineered Saccharomyces cerevisiae strains to express either different parasite drug targets [ 9 ], or their equivalent human proteins, such that the growth of the yeast is dependent on the functioning of these heterologous proteins.…”
Section: Introductionmentioning
confidence: 99%